Improving lithium battery cooling: analyzing the impact of air flow, nanofluid flow, and phase change materials - Mustafa, Jawed; Alqaed, Saeed; Sajadi, S. Mohammad; Aybar, Hikmet Ş. (Frontiers in Energy Research, 2024)
In this study, a finite element analysis is employed to numerically investigate the thermal behavior of a battery pack comprising cylindrical lithium-ion cells. The system incorporates air cooling with phase change material (PCM) surrounding the batteries and nanofluid (NFD) circulating within the PCM through tubes of varying diameters (ranging from 2 mm to 6 mm) at flow rates (FRT) spanning 5 mL/min to 20 mL/min. A two-phase mixture model is applied to analyze the behavior of the NFD as it changes phase. The transient simulation covers a 1-h period to assess temperature variations of the NFD, batteries, surrounding air, PCM, and the phase change process within the PCM. Our results indicate that variations in NFD flow rate (NFFR) do not significantly affect the PCM’s molten fraction during PCM melting, coinciding with an increase in battery temperature (TBT). However, during the PCM refreezing phase, a FRT of 15 mL/min results in the highest quantity of solid PCM. The outlet temperature (TOT) of the NFD demonstrates a cyclical pattern of increase and decrease over time. We observe that when the NFD temperature is elevated, the lowest TOT of the NFD is associated with a FRT of 5 mL/min. Conversely, when the NFD temperature is lowered, this FRT leads to the highest TOT of the NFD. The TBT exhibits some sensitivity to changes in FRT within the initial half-hour, with a subsequent decline, particularly with a FRT of 15 mL/min.